INFORMATION SYSTEMS USING SOFT SYSTEM METHODOLOGY AT BPD EAST NUSA TENGGARA - Raymond Elias Mauboy; Kristoko Dwi Hartomo; Irwan Sembiring (Informatika, Universitas Jenderal Soedirman, 2022)
The provision of targeted funds is important, especially for banking institutions. In order to be able to channel funds properly, banks need to select proposals for assistance requests addressed to the Bank. the criteria requested this is a problem that occurs in the East Nusa Tenggara Regional Development Bank (BPD NTT). The purpose of the Fund Assistance Proposal is for Parties to be able to provide Assistance in the form of Funds or goods to Applicants for Proposals SSM It is a structured approach system to understand the problem, so that it can know the steps that will be taken to overcome the problem and carry out a process which is a more humane and highly efficient system modeling taking into account various aspects of behavior, both organizational behavior and human behavior in complex conditions where there are different points of view on the definition of problems on soft problems or problems related to organizational and human behavior which are not deterministic, but probalistic. In addition, this method builds a conceptual model that is useful for identifying problems so that the right decision-making process can be carried out. In doing so there are 7 steps that will be carried out which are useful for the process of comparing the problem situation in order to identify the most feasible changes and using CATWOE Analysis to understand the different points of view that each stakeholder has together in the organization, every problem has a solution. but whether the answer is appropriate for the organization or not this is an advantage of CATWOE. The results of these stages will be in the form of a support system for a better future system process.